Peran Filsafat dalam Lembaga Pendidikan Islam di MTs Al Kahfi Surakarta (Studi Analisis Ontologi, Epistemologi, dan Aksiologi) - Yadi, Yadi; Yaman, Nur; Mujiburrohman, Mujiburrohman (Lembaga Yasin AlSys, 2025)
This study aims to analyze the role of philosophy within the Islamic education system at MTs Al Kahfi Surakarta through the lenses of ontology, epistemology, and axiology. Fundamentally, Islamic educational institutions serve not only as channels for knowledge transmission but also as spaces for shaping holistic individuals who are faithful, knowledgeable, and virtuous. The research employed a qualitative case study method, utilizing observation, in-depth interviews, and documentation, with data analyzed using the interactive model of Miles and Huberman. The findings reveal that ontological values are reflected in the view of students as both spiritual and social beings; epistemological values are embodied in the integration of revelation and reason within the learning process; while axiological values are evident in the orientation of education toward character formation, morality, and social responsibility. Although these philosophical values are implicitly integrated, their implementation faces challenges such as limited philosophical awareness among educators, curriculum dualism, and the dominance of academic standardization. Nevertheless, strategic opportunities remain through the school’s religious culture, integrated curriculum, and the openness of young educators to Islamic intellectual innovation. This study recommends strengthening teachers' philosophical competence and developing value-based Islamic educational institutions through systematic and reflective approaches.